Health products' and substance use among pregnant women visiting a tertiary hospital in Belgium: A cross‐sectional study. Issue 9 (25th July 2019) - Ceulemans, Michael; Van Calsteren, Kristel; Allegaert, Karel; Foulon, Veerle
Abstract: Purpose: To investigate the prevalence and type of health products used among pregnant women visiting a tertiary hospital in Belgium, as well as who advises these products, where women buy these products, which determinants are associated with medication and pregnancy vitamin intake, and preconception lifestyle changes such as folic acid intake and substance use. Methods: A cross‐sectional study was performed at the outpatient obstetrics clinics of the University Hospital Leuven, Belgium between November 2016 and March 2017. All pregnant women 18 years and older and understanding Dutch, French, or English were asked to participate in an online survey. Results: In total, 379 pregnant women participated. Prevalence of medication use during the preceding week was 52%. Paracetamol (14%), levothyroxine (13%), and antacids (9%) were the most frequently used medicines. Pregnancy vitamins were used by 86% of women, and 97% had used a pregnancy vitamin somewhere during pregnancy. Only 56% initiated folic acid supplementation at least 1 month before pregnancy. Preconception use of folic acid among women following assisted reproductive technology was 73%. Inappropriate use of health products was observed among 3% of women. Prevalence of alcohol use and/or smoking during the preceding week was 6%. Alcohol and smoking cessation mainly occurred after pregnancy diagnosis. Conclusion: Pregnant women living in Belgium frequently use medicines, pregnancy vitamins, and other health products. Preconception lifestyle changes such as folic acid intake and alcohol and smoking cessation are poorly implemented. Public campaigns and interventions are needed to improve preconception care and counselling.